(Non-)fictitious war experiences and war stories - Horváth, Andrea (Ethnographica et Folkloristica Carpathica, 2020)
The First World War not only destroyed almost all life, it also restructured established traditions and structures and completely redefined social relations. In my contribution I try to present the generation and time experience of that time by examining in more detail the reactions of German intellectuals to the shattering of occidental values. It is about the crisis of the monarchical principle, the call for democratization, the experience of death and the evaluation of knowledge.